RECONSTRUCTING PATRIARCHAL DOMINATIONS AND GENDER ROLES IN DEBORAH ELLIS AND RUKHSANA KHAN WORKS - Suparti, Erni (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2015)
This study analyzes the issues of traditional patriarchy and the reconstruction of gender roles of three books; The Breadwinner (Deborah Ellis), Parvana’s Journey (Deborah Ellis), and Wanting Mor (Rukhsana Khan). All these three books are considered as multicultural literature because of the theme of war and violence in Afghanistan culture. The findings confirm gender roles are unstable and inconstant. These three books show evidences of how gender roles are adaptable and changeable depends on what gender is favored in the social interactions. What is more, the institutional perspectives provide ways of reasoning gender roles are altered and changed. By observing Afghan social practices and policies in their culture, these books also confirm that most social institutions in this culture are gendered to favor patriarchy dominations. Therefore, the main characters of these books portray the shifts and changes of their gender roles to save them from ‘disparate treatment’ in the society.Key word: patriarchal dominations, gender roles, Afghanistan culture